Holiness, War, and Peace: Ancient Jewish Traditions Concerning the Landscape and Ecology of Jerusalem and Its Environs in the Second Temple Period - Shemesh, Abraham Ofir (Religions, 2018)
The Second Temple period is considered both a pinnacle and a low point in the history of Jerusalem. One manifestation of the sharp fluctuations in Jerusalem's status is its flora and ecology. The current study aims to address the historical events and the Talmudic traditions concerning the flora and landscape of Jerusalem. In the city's zenith, the Jewish sages introduced special ecological regulations pertaining to its overall urban landscape. One of them was a prohibition against growing plants within the city in order to prevent undesirable odors or litter and thus maintain the city's respectable image. The prohibition against growing plants within the city did not apply to rose gardens, maybe because of ecological reasons, i.e., their contribution to aesthetics and to improving bad odors in a crowded city. In the city's decline, its agricultural crops and natural vegetation were destroyed when the beleaguered inhabitants were defeated by Titus' army. One Talmudic tradition voices hope for the rehabilitation of the flora (shitim) around the city of Jerusalem. Haggadic-Talmudic tradition tries to endow Jerusalem with a metaphysical uniqueness by describing fantastic plants that allegedly grew in it in the past but disappeared as a result of its destruction.